Gardens of the Gilded Age Nineteenth-Century Gardens and Homegrounds of New York State - Doell, M (Syracuse University Press, 1986)
Houses and gardens created in America between 1860 and 1917 were "modern" manifestations of nineteenth century art, science, and industry, conveying cultural values in their form, function, style, and materials. Now Increasing public interest in the restoration of nineteenth-century properties has provoked curiosity about their physical surroundings. While many buildings from the period survive intact, their landscape and garden settings, in most cases, have long since disappeared. Natural cycles of growth and decay, together with manmade changes, have left only remnants of the historic landscape - a dilapidated fence post, the arching canopy of a venerable tree, some persistent spring bulbs at a dooryard, Based on a careful study of historic photographs from museums, libraries, archives, and private collections, Gardens of the Gilded Age explains the history, design, and social function of ornamental gardens and homegrounds in New York State during the latter parts of the nineteenth century. As early as 1820, New York State had become the nation's leader in population, foreign and domestic commerce, transportation, banking, and manufacturing. New York also took the lead in influencing the rest of the nation in the theory and practice of horticulture and landscape gardening. The more than one hundred photographs featured in Gardens of the Gilded Age were not selected for their aesthetic quality alone, or for their uniqueness. While including magnificent proprieties such as Sonnenberg, Lorenzo, and Box Hill, many show ordinary gardens which reflect the character of common people in the art and craft of garden making. Taken together, these garden photographs provide a new perspective on American customs in landscape gardening from 1860 to 1917.